Evaluation of low - cost lining materials for field channels - ABDU MUDESIR ISSA; Er. Rema K. P (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
Evaluation of low - cost lining materials for field channels
Evaluation of low - cost lining materials for field channels